Effects of low- and high-frequency electroacupuncture on protein expression and distribution of TRPV1 and P2X3 in rats with peripheral nerve injury. Issue 5 (October 2021) - Du, Junying; Fang, Junfan; Xiang, Xuaner; Yu, Jie; Le, Xiaoqin; Liang, Yi; Jin, Xiaoming; Fang, Jianqiao
Background: Whether electroacupuncture (EA) stimulation at different frequencies has a similar effect on spared nerve injury (SNI) as other neuropathic pain models, and how EA at different frequencies causes distinct analgesic effects on neuropathic pain is still not clear. Methods: Adult male Sprague-Dawley rats were randomly divided into sham SNI, SNI, 2 Hz, 100 Hz and sham EA groups. Paw withdrawal threshold (PWT) and paw withdrawal latency (PWL) were measured. EA was performed once a day on days 1 to 14 after SNI. The expressions of transient receptor potential cation subfamily V member 1 (TRPV1) and peripheral purinergic P2X receptor 3 (P2X3) were determined by western blotting and immunofluorescence. TRPV1 siRNA and P2X3 siRNA were administered by intrathecal injection. TRPV1 or P2X3 agonists were combined with EA. Results: There were significant decreases in PWT, but no changes in PWL in the 14 days after SNI. EA using 2- or 100-Hz stimulation similarly increased PWT at every time point. The cytosol protein expression of P2X3 in the L4–L6 dorsal root ganglia (DRG) increased, but the expression of TRPV1 decreased in the SNI model. Both these effects were ameliorated by EA, with 2-Hz stimulation having a stronger effect than 100-Hz stimulation. Blocking either TRPV1 or P2X3 specific siRNAs attenuated the decreased PWT induced by SNI. Administration of either a TRPV1 or P2X3 agonist inhibited EA analgesia. Conclusion: 2- and 100-Hz EA similarly induced analgesic effects in SNI. This effect was related to up-regulation and down-regulation, respectively, of cytosol protein expression of P2X3 and TRPV1 in L4–L6 DRG, with 2 Hz having a better effect than 100 Hz.